(untitled) (Bangladesh Journal of Medicine, 2024)
Background: ABO Blood Group discrepancy means the difference between forward and reverse grouping due to an unexpected extra reaction or a missing reaction. This is one of the major reasons for a transfusion reaction. The aim of this study was to analyze ABO blood group discrepancies in an algorithmic manner and find out the risk factors among the recipients. Methods: This crosssectional observational study was carried out among 200 patients in the Department of Transfusion Medicine, BSMMU, Dhaka, for a period of 6 months. Both forward and reverse blood grouping were done among the recipients’ sample and risk factors related to ABO grouping discrepancies was evaluated. Results: Presence of ABO discrepancies were found in 5.5% blood recipients (n=11). Among them the major risk factors were transfusion dependent thalassemia (TDT), mismatched transfusion, autoimmune hemolytic anemia (AIHA) and multiple myeloma (2 patients in each category, 1% each). Furthermore, 83.0% recipients were having blood transfusion d”5 times. Conclusion: Despite all precautions ABO discrepancies still exist in transfusion sectors. Conditions where chance of ABO discrepancy is high needs extra precautions before ABO grouping to ensure safe blood transfusion. Bangladesh J Medicine 2025; 36: 43-49